Exploring the Implementation of Think-Pair-Share Strategy in Speaking class (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research aimed to describe the ninth-grade student engagement in the implementation of the Think-Pair-Share strategy in speaking class and to describe the strengths and weaknesses of the Think-Pair-Share strategy in speaking class of ninth-grade students at SMPN 9 Sungai Kakap. Think Pair Share is a component of cooperative learning strategies, fostering an environment where students initially reflect individually, and then collaboratively engage in discussion and problem-solving within their group. The study was carried out using qualitative research techniques with the English teacher and students as the subjects of the research. Data was collected through both observation and interviews. The data collection process was comprehensive and involved two primary methods: observation and interviews. Observations were used to answer the first research question, while interviews were used to answer the second research question. The results of this study included: 1. The implementation of the Think-Pair-Share strategy effectively can help students to actively engage in the learning process, it showed the students have actively participated during the speaking learning-teaching process. 2. The Think-Pair-Share approach positively influences students, as follows; building their critical thinking, increasing active engagement, fostering collaboration sense, and boosting their confidence. Think-Pair-Share also provided the students with opportunities to practice their speaking skills, and they also got immediate feedback from the teacher. The researcher discovered certain weaknesses in the Think-Pair-Share strategy: it does not align with every student’s learning style, and some students tend to become overly reliant on their peers.